Cytomegalovirus Diagnosis in Lung Transplantation: Validation of a qPCR Cutoff in a Reference Transplant Center in Brazil - Castelo, Ana Carolina; Barbosa, Lorenna Maria Oliveira; Nascimento, Douglas Zaione; Pinheiro, Camila Bertoldo; Severini, Maria Fernanda Aquino; Kayser, Marisa Gutjahr; Fossá, Aline; Ingrassia, Rafaela; Mello, Karina Faccio; Moro, Luana; Toniolo, Pâmela Coutinho; Santos, Nathalia Pereira; et al. (Brazilian Journal of Transplantation, 2026)
Objectives: Cytomegalovirus (CMV) infection is a significant complication in lung transplant recipients. Although quantitative polymerase chain reaction (qPCR) is internationally recommended for CMV monitoring, pp65 antigenemia remains widely used in Brazil due to economic and structural constraints within the public healthcare system. Establishing a locally validated qPCR cutoff aligned with current institutional practice is essential to support a safe and sustainable transition to molecular diagnostics in this setting. Methods: This retrospective study included 80 adult lung transplant recipients at Santa Casa de Porto Alegre, a major transplant center in southern Brazil, from April to December 2023. All patients underwent both pp65 antigenemia and qPCR testing. Receiver operating characteristic (ROC) curve analysis was performed using antigenemia (> 3 cells/100,000 granulocytes) as the reference method to determine the optimal qPCR cutoff for positivity. Results: ROC analysis identified an optimal qPCR cutoff of 3.75 log IU/mL (≈ 3,162 IU/mL), with an area under the curve of 0.91, 100% sensitivity, and 82.6% specificity. The proposed threshold demonstrated excellent discriminatory performance for CMV detection in this population. Conclusion: The locally defined cutoff of 3.75 log IU/mL provides an objective reference for interpreting qPCR results in Brazilian lung transplant programs where antigenemia remains in use in many centers. These findings offer practical, real-world evidence to guide institutional CMV surveillance strategies and support the gradual and economically sustainable integration of molecular monitoring in low- and middle-income countries.